Emotional intelligence and its relationship to self-confidence The children of Riyadh (Journal of the College of Basic Education, 2022)
The research aims at the following: __ Measuring emotional intelligence among kindergarten children in general (males and females)_ Measuring self-confidence among kindergarten children in general (males and females)Knowing the significance of the difference in emotional intelligence according to the gender variable (male and female)